EFFECTIVE MANAGEMENT AND OPTIMIZATION OF BUSINESS PROCESSES - Bezdelov, V.; Kalinin , A.; Sultanova, B. (Scientific Journal of Astana IT University, 2020)
This article discusses the problems of introducing an effective business, as well as optimizing business processes. Various approaches to managing and optimizing business processes are analyzed. The reasons for which it is necessary to improve the process and each component of this process are identified and described. Two main approaches to improving business processes are considered: functional and approach, the main differences between them, as well as the advantages and disadvantages of each of them are demonstrated. Any process has a life cycle, thanks to which it follows; the article considers the life cycle of six sigma. Based on the material studied, methods for improving business processes are proposed, and the role of the leader is examined, and concepts such as creative management and a creative manager are examined and what their role is in modern business. Any life cycle needs modeling, timely improvement, so that the company can get good results, so managers and chief managers must follow the simple rules discussed in the article in order to simulate the business process “as is” and “as it should be” , you can use the Business Process Management Notation and special software designed for this. The general conclusion of the article is that each company should choose its own approach and method of optimizing business processes based on general principles.